High temperature superconducting microwave devices - Kale, K; Kale, Kedaar S. (1996)
﻿ This thesis describes investigations into the application of high temperature superconductoRs(HTS) for microwave devices. The ultimate aim of this research was to produce HTS components that would demonstrate the commercial potential of their use in spacecraft such as satellites or in base stations for terrestrial cellular communication systems. During the course of this research the surface resistance (Rs) of HTS thick and thin films deposited onto different substrates has been measured by a variety of techniques. These have been compared and contrasted with each other. There has been a particular emphasis upon the use of dielectric resonators as characterization tools and this thesis describes their use to measure the Rsof films and the loss tangents of the materials used in them. Consideration has been given to losses in the walls of the enclosures that surround dielectric resonators which is an area that has been neglected in previous work. Many of the films characterized had Rs values lower than normal conductoRsat the same temperature and frequency including a thick film which had an Rsof 2.7mΩ±8.0% at 77K and scaled to 10 GHz which represents the second lowest result achieved in a thick film to date. Using such high quality films a number of devices have been made including microstrip resonatoRsoperating at 1.7-8.4 GHz, 5.58 GHz, 23 GHz and 24.75 GHz dielectric resonatoRsand filteRswith centre frequencies from 5.58-13 GHz. Such devices have shown performance enhancements of up to 700% over their normal conductor equivalents. Benefits have been delivered in light, low volume packages which is of particular advantage to the satellite communications industry. Finally, there has been a demonstration, for the first time, of a tunable HTS thin film filter.